Takhrij and Syarah Hadith of Chemistry The Hadith Point of View of the Iron Phenomenon and Its Benefits - Ali Fahd; Wahyudin Darmalaksana; Rosihon Anwar; Assyifa Junitasari (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet Muhammad Saw. about the hadith's point of view on iron. This research method is qualitative through the takhrij and sharah hadith approaches with chemical analysis. The results and discussion of this research are about the phenomenon of iron rusting and also about the benefits of iron in all aspects of life. This research concludes that the presence of iron is at the same time a phenomenon that has existed since the time of the Prophet Muhammad Saw. brings many benefits in human life based on takhrij and sharah hadith. This study recommends developing the benefits of iron through chemistry